Diseño de una herramienta digital que permita la estimación de la velocidad óptima y el ángulo de bajada del equipo bes para su correcta instalación en fondo, minimizando el daño mecánico del cable de potencia (2019)
In this thesis it is presented a digital tool (ANGVEL) that estimates the optimal velocity and the positioning angle of the ESP tool for its correct installation downwards, minimizing mechanical damage of the power cable. For this study, 32 well trajectories were analyzed on the effect that this geometry has on the failure recurrence of the power cable of ESPs. During the analysis it was observed that both angles, inclination and azimuth change, affect the integrity of the tool when installing downwards, reason why it was considered the DLS as the best parameter to recommend velocity.